Improved DSVPWM strategy for transformerless three-level grid-connected inverter. (July 2020) - Li, Zhang; Sun, Junbin
Abstract: Aiming at the leakage current problem in the transformerless three-level grid-connected inverter, an equivalent model of the common-mode circuit is established, and the analysis shows that in addition to the common-mode voltage, the fluctuation of the neutral point voltage is also an important reason for the leakage current. Therefore, an improved DSVPWM strategy is proposed, which introduces a non-basic vector in the same sector as the synthesized reference vector. This not only makes up for the shortcomings of the traditional DSVPWM strategy that cannot balance the neutral point voltage due to the lack of redundant vectors, but also retains the advantage of halving the common-mode voltage amplitude in the traditional strategy, because this introduced vector is the basis vector for other sectors. In order to prevent the total vector action durations from overflowing and reasonably allocate the duration of each vector action, a corresponding neutral point voltage balance algorithm is designed, so that the neutral point voltage is effectively controlled, and the leakage current is greatly attenuated. Simulation results verify the effectiveness of the proposed improved modulation strategy.